Предмет: Алгебра,
автор: theimarrysvikk
найдите f'(-5) если f(x)=(x+4)^6+(x+6)^4
Ответы
Автор ответа:
1
Ответ:
2
Объяснение:
f(-5)=(-5+4)^6+(-5+6) ^4=(-1)^6+1^2=1+1=2
Автор ответа:
1
f(-5) значит что вместо х мы ставим значение -5
f(-5)=(-5+4)⁶+(-5+6)⁴
f(-5)=(-1)⁶+1⁴
f(-5)=1+1
f(-5)=2
Ответ: 2
Похожие вопросы
Предмет: Английский язык,
автор: lenarik05
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: anglinakerimova
Предмет: Алгебра,
автор: meuz
Предмет: География,
автор: Smekalina